The comparative effect of corruption and piketty’s second fundamental law of capitalism on inequality - Fakir, Adnan M.S.; Ahmad, Azraf Uddin; Hosain, K M Masnun; Gani, Ridhim Sadman; Hossain, Mostafa Rafid (2016)
The definite version of the draft working paper is available at: http://www.ergonline.org/seminar/document/2nd_summer_conf/The%20Comparative%20Effect%20of%20Corruption.pdf